Successful Outcome of Pregnancy with Large Fibroid Uterus- A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background: Fibroid is the most common of all pelvic tumours, being present in 20 percent of  women in the reproductive age group and increases with age.Obstetric cesarean hysterectomy  is mostly done for indications deemed to be serious and life threatening to the patient and not  amenable to conservative management.Case: A 27 years old lady was admitted in BSMMU with 3rd gravida 35 wks pregnancy with  less fetal movement with fibroid uterus. Fibroid was diagnosed at her 21 weeks pregnancy by  ultrasonogram. Caesarean section was done at 35+ weeks of pregnancy because of nonreactive  CTG. After delivery of the baby and placenta, severe bleeding started. Caesarean hysterectomy  was done. The mother and baby were healthy at the time of discharge.Conclusion: Very few patients needed cesarean hysterectomy in case of fibroids in pregnancy. However there is no question that cesarean hysterectomy save lives especially in case of  bleeding that cannot be controlled by simpler measures. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13746 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 87-89